A new signal reconstruction method in compressed sensing. (July 2018) - Chen, Xuan
Abstract: Aiming at the shortcomings of being rough by using the l 1 norm to replace the original signal for signal reconstruction, this paper first constructs the l 1 norm's smooth approximation function and studies the monotonicity and convergence of the optimal solution sequence. Second, the pseudo-function || x || p (0 < p < 1) replaces || x ||1 in signal reconstruction, and the maximum entropy function is used to smooth lp (0 < p < 1). In this paper, the algorithm's performance is analyzed and its feasibility is verified using one- and two-dimensional signal reconstruction. This algorithm has smaller error than other compression reconstruction algorithms, better structure, and a more convenient calculation.